IMPLEMENTASI KEBIJAKAN E-GOVERNMENT DALAM PENINGKATAN MUTU PELAYANAN PUBLIK DI KOTA BANDUNG - Poni Sukaesih Kurniati; Ranti Tri Gislawati; Faiza Nur Safitri; Arijal Julhaijan Lutpi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The purpose of this study was to analyze the implementation of e-Government policies in improving the quality of public services in Bandung City. Methods taken using secondary data taken from previous journals, books, articles, theses, theses, dissertations and news on the internet that have been researched using a qualitative approach with the method of literature study or literature review. The results of this study are E-Government in Bandung City, its information system services are quite good but in terms of resource indicators and disposition are still lacking. The impact is that services in the city of Bandung have become at least effective with the e-Government policy. The conclusion is that the development of E-Government in Bandung City in its information system services is quite good but it needs to be noted again that there are still many people who do not know how to use it.